Online Learning Management During the Covid 19 Period (Descriptive Study At 5 Elementary Schools In Karawang Regency) - Fauziah, Sifa; King Muttaqien, King; Koswara, Nandang (CV. Inara, 2022)
The research in the form of a dissertation is entitled